Neonatal NET-Inhibitory Factor improves survival in the cecal ligation and puncture model of polymicrobial sepsis by inhibiting neutrophil extracellular traps - de Araujo, Claudia V.; Denorme, Frederik; Stephens, W. Zac; Li, Qing; Cody, Mark J.; Crandell, Jacob L.; Petrey, Aaron C.; Queisser, Kimberly A.; Rustad, John L.; Fulcher, James M.; Evangelista, Judah L.; Kay, Michael S.; et al. (Frontiers in Immunology, 2023)
Neutrophil extracellular traps (NETs) clear pathogens but may contribute pathogenically to host inflammatory tissue damage during sepsis. Innovative therapeutic agents targeting NET formation and their potentially harmful collateral effects remain understudied. We investigated a novel therapeutic agent, neonatal NET-Inhibitory Factor (nNIF), in a mouse model of experimental sepsis – cecal ligation and puncture (CLP). We administered 2 doses of nNIF (1 mg/kg) or its scrambled peptide control intravenously 4 and 10 hours after CLP treatment and assessed survival, peritoneal fluid and plasma NET formation using the MPO-DNA ELISA, aerobic bacterial colony forming units (CFU) using serial dilution and culture, peritoneal fluid and stool microbiomes using 16S rRNA gene sequencing, and inflammatory cytokine levels using a multiplexed cytokine array. Meropenem (25 mg/kg) treatment served as a clinically relevant treatment for infection. We observed increased 6-day survival rates in nNIF (73%) and meropenem (80%) treated mice compared to controls (0%). nNIF decreased NET formation compared to controls, while meropenem did not impact NET formation. nNIF treatment led to increased peritoneal fluid and plasma bacterial CFUs consistent with loss of NET-mediated extracellular microbial killing, while nNIF treatment alone did not alter the peritoneal fluid and stool microbiomes compared to vehicle-treated CLP mice. nNIF treatment also decreased peritoneal TNF-α inflammatory cytokine levels compared to scrambled peptide control. Furthermore, adjunctive nNIF increased survival in a model of sub-optimal meropenem treatment (90% v 40%) in CLP-treated mice. Thus, our data demonstrate that nNIF inhibits NET formation in a translationally relevant mouse model of sepsis, improves survival when given as monotherapy or as an adjuvant with antibiotics, and may play an important protective role in sepsis.